A cross cultural study of firms with joint ownership : a study of Swedish multinational corporations in newly industrialized countries / Nick Kavoosi and John C. Mc Intosh (Faculty of Business and Management ; UiTM Press, 1996)
This paper examines the effect of cultural differences on organizational effectiveness between Swedish firms and Asian partners in Newly Industrialized Countries. Drawing on Hofstede's (1984) dimensions of culture, the study noted large dissimilarities between sample firms on the dimensions of individualism-collectivism, power distance, uncertainty avoidance, and masculinity-femininity. Respondents in the study generally reported satisfaction with the venture's performance. The study discovered, however, that centralized planning in conjunction with an autocratic management style on the part of the Swedish partner caused a less favorable evaluation.